A visual training tool for teaching kanji to children with developmental dyslexia. Issue 1 (2nd January 2016) - Ikeshita-Yamazoe, Hanae; Miyao, Masutomo
Abstract : We developed a visual training tool to assist children with developmental dyslexia in learning to recognize and understand Chinese characters (kanji). The visual training tool presents the strokes of a kanji character as separate shapes and requires students to use these fragments to construct the character. Two types of experiments were conducted to investigate the differences between the effects of the visual training tool and a traditional Japanese teaching method – shi-sha-ho, which consists of copying a visually displayed model – on developmentally dyslexic children's kanji writing skills. Six Japanese children with developmental dyslexia (7–11 years old) and 58 controls (7–8 years old) participated in the first experiment. Participants used both the visual training tool and the shi-sha-ho . We found that the visual training tool was more effective than the shi-sha-ho for use with Japanese children with developmental dyslexia in learning kanji, both just after the experiment was completed and four weeks later. In the second experiment, we asked four participants with dyslexia to use the visual training tool at home for four weeks prior to the second experiment once a week for four weeks. Participants learned one kanji character each week during the two weekly sessions for a period of eight weeks using the visual training tool. The post-tests were conducted four and eight weeks after the experiment. Participants' retention of the target kanji was at least up to eight weeks. Results of the second experiment showed the visual training tool developed in the present study have shown the possibility of becoming a promising tool for children with developmental dyslexia.